The Impact of Raw Material Shortage and Increasing Freight Cost to Dell’s Supply Chain Implementation - Nathasya Fernanda; Lena Ellitan (CV. Ulil Albab Corp, 2023)
Dell is the huge technology company that is well known with its strength in supply chain strategy. The capability to respond to the environment change can make them sustain for the long time. At first, direct sale and customization were the remarkable strategies of Dell. However, it led to the low level of product availability. As time passed, consumers require the higher availability products that cause Dell also starts to establish the standard products and sell them in stores. Regardless from the success of Dell’s supply chain, this company also faces the challenges such as the shortage of network controller and micro controller which are used for making personal computer. More than that, the increasing the freight cost is also faced by Dell as the result of the COVID-19 pandemic era. Fortunately, the supply chain that has been designed to achieve the goal to present a unique positioning, high innovative products with affordable prices can save this company. Dell’s strategic fit, the supply chain’s driver, the distribution network, the presence of e-business contributes to solve these supply chain’s problem. In addition, the writer suggests to digitize supply chain and establish the long term relationship to prevent the similar case happen in the future.